The Impact of IEEE 802.11 Contention Window on The Performance of Transmission Control Protocol in Mobile Ad-Hoc Network - Ali, Iqtidar; Hussain, Tariq; Khan, Kamran; Iqbal, Arshad; Perviz, Fatima (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2020)
A Mobile Ad-hoc Network (MANET) is a group of nodes connected via ad-hoc fashion for communicating with each other through wireless interface. The communication among the nodes in such network take place by using multi-hop in the absence of fixed infrastructure. TCP faces some hurdles and complexities in multi-hop ad-hoc networks particularly congestion and route failures. The incompatibility between the MAC and TCP are previously noticed by the research community. This research study focuses on the impact of MAC layer contention window on TCP in MANET by using variation in network density and velocity of nodes respectively. Simulation has been carried out to quantify and analyze the impact of Contention Window (CW) sizes that affects the performance of TCP by using NS-2 simulator. The impact of CW is investigated on TCP in multi-hop networks by means of performance evaluation parameters i.e. average delay, average packet drops and average throughput.